Deep dive iOS 16 Swift : SwiftUI programming. (Packt Publishing, 2023)
This beginner-to-advanced course focuses on iOS 16 programming using the Swift language and SwiftUI framework. This project-based course teaches about the features of the language and creating apps using the MVVM software design pattern hand in hand with SwiftUI and iOS 16 development. You will learn to efficiently use Xcode 14, navigate, and use hotkeys and code snippets. The course covers fundamentals of iOS and then uses this to create apps as possible using these basics. We will explore programming basics, that is, variables, constants, arrays, loops, structs, conditionals, basic data types, guard, tuples, and enumerations. We will then advance to HStack, VStack, ZStack, gradients, colors, text, alignment, frames, rotations, grids, images, and AsyncImage. We will examine working with code snippets to write programs more efficiently. We also cover useful topics in these sections such as page tabbed views, background colors, buttons, gradient text and masks, nice default views, avatars, clickable images that link to a website, and so on. Upon completion of the course, you will create apps independently like the greetings app, tip calculator, recipes app with MVVM pattern, Fizz Buzz, alarm app, Conway's Game of Life, Brevis app iOS development, multilingual animals, and various user interfaces. What You Will Learn Learn the iOS 16/SwiftUI programming language fundamentals Learn HStack, VStack, ZStack, colors, text, frames, grids, and images Learn to efficiently use Xcode 14, hotkeys, and code snippets Learn to add hypertext markup language (HTML) to color extensions Create Brevis, quote of the day, mystic puzzle, and Speed code apps Build user interfaces for body shape, meditation, finance, and tasks Audience This course caters to individuals wishing to acquire application development skills using SwiftUI/iOS 16 with beginner to advanced programming skillsets; however, more than basic to intermediate programming skills are desirable at least to make the most of the course. Anyone wishing to learn programming on iOS 16 using SwiftUI and individuals wanting to learn a quick course on what can be developed using SwiftUI would benefit from this course. About The Author Ron Erez: Dr. Ron Erez is a computer programmer, educator, and mathematician. Dr. Erez has been programming for over 30 years and has always been amazed by the creativity and satisfaction of writing computer programs. Dr. Erez is also an experienced teacher, teaching mathematics, computer science, and English literature from middle school to university level courses. Dr. Erez is out cooking, cleaning, skateboarding, and living in his free time.